2022
DOI: 10.3389/fpsyg.2022.802477
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Physical Activity, Parental Psychological Control, Basic Psychological Needs, Anxiety, and Mental Health in Chinese Engineering College Students During the COVID-19 Pandemic

Abstract: The issue of mental health among college students is of increasing concern during the COVID-19 outbreak. Since course characteristics of engineering college students determine the particularities of their mental health, the specific objectives of this study were: (1) to analyze the relationship between physical activity, parental psychological control, basic psychological needs, anxiety, and mental health in Chinese engineering college students during COVID-19 pandemic; and (2) to examine the mediation effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Higher levels of psychological need satisfaction were linked to lower levels of depression and generalized anxiety disorder, according to a meta-analysis [48]. Generalized anxiety disorder levels decrease, and mental health is enhanced when basic psychological needs are satisfied [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of psychological need satisfaction were linked to lower levels of depression and generalized anxiety disorder, according to a meta-analysis [48]. Generalized anxiety disorder levels decrease, and mental health is enhanced when basic psychological needs are satisfied [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…This is different from the findings of previous studies, and it has been suggested that this may be due to the fact that females are more concerned about their safety and risks. 18 Psychological problems resulting from risk perception in adolescents are closely related to gender as well as the social messages they are exposed to.…”
Section: Discussionmentioning
confidence: 99%
“…Participants rated each item on a 5-point-Likert scale ranging from 0 (not at all) to 4 (extremely), with higher score indicating more severe social anxiety symptoms. This measure has been widely used in Chinese university populations and has shown good reliability and validity ( 29 ). The Cronbach’s alpha coefficient of this scale displayed good reliability in the current study (Cronbach’s α = 0.934).…”
Section: Methodsmentioning
confidence: 99%